Immunohistochemical Expression of Cyclooxygenase-2 in endometrioid carcinoma - Kavi Kamaran Abbas; Jalal Ali Jalal (Advanced Medical Journal)
Background and objectives: Cyclooxygenase-2 functions as an enzyme which synthesize prostaglandins from Arachidonic acid Cyclooxygenase -2 is one of the important factors in maintaining the endometrium during menstrual cycle. The Aim of this study was to assess expression of Cyclooxygenase-2 in endometrioid carcinoma by immunohistochemistry to explore association between Cyclooxygenase-2 expression and a certain number of clinicopathologic variables.